Imagining asylum, governing asylum seekers: Complexity reduction and policy making in the UK Home Office. (25th September 2017) - Mayblin, Lucy
Abstract: Drawing on elite interviews with UK asylum policymakers, this article entails a detailed elaboration of how policy programmes are produced by particular ways of imagining asylum seeking in an effort to reduce the complexity of the phenomenon and thus devise policy responses to it. The article explores how such processes can lead to the curtailment of the economic rights of asylum seekers with specific reference the UK policy of severely restricting labour market access for asylum seekers. The policy imaginary—the story which is utilized in reducing the complexity of irregular migration in this context—is the idea of the 'economic pull factor'. That is that disingenuous asylum seekers (economic migrants in disguise) are 'pulled' to particular countries by economic opportunities. This construal of what drives irregular migration for asylum is not natural or inevitable, it is the outcome of institutionally embedded ways of viewing the world and Britain's place within it. This discussion brings insights from critical policy studies to bear on asylum policy making, offering new ways of understanding the practices and processes of policy making in this field.